A Simple and Efficient Method to Isolate LTR Sequences of Plant Retrotransposon. (6th May 2014) - Guo, Da-Long; Hou, Xiao-Gai; Zhang, Xi
Abstract : Retrotransposons (RTNs) have important roles in the formation of plant genome size, structure, and evolution. Ubiquitous distributions, abundant copy numbers, high heterogeneities, and insertional polymorphisms of RTNs have made them as excellent sources for molecular markers development. However, the wide application of RTNs-based molecular markers is restricted by the scarcity of the LTR (long terminal repeat) sequences information. A new, simple, and efficient method to isolate LTR sequences of RTNs was presented based on the degenerate RNase H nested primers and PPT (polypurine tract) primer of RTNs in tree peony. This method combined the characteristics and advantages of high-efficiency thermal asymmetric interlaced PCR (hiTAIL-PCR), annealing control primer (ACP) system, and suppression PCR method. Nineteen LTR sequences were isolated using this new method in tree peony and the applicability of the LTR sequences based markers was validated by further SSAP analysis. The results showed that the new method is simple, of low-cost, and highly efficient, which is just conducted by three rounds of PCR and does not need any restriction enzymes and adapters, much less the hybridizations. This new method is rapid, economical, and cost- and time-saving, which could be easily used to isolate LTR sequences of RTNs.